1996
DOI: 10.1038/sj.bdj.4809263
|View full text |Cite
|
Sign up to set email alerts
|

The single unit, single retainer, cantilever resin-bonded bridge

Abstract: Resin-bonded restorations have many advantages over conventional alternatives. Advances in adhesive technology together with a better understanding of the clinical function of such restorations have allowed resin-bonded bridges to play an important role in everyday clinical practice. This paper highlights the role and importance of the single abutment, single pontic cantilever resin-bonded bridge. Clinical experience might suggest that the cantilever design offers a viable alternative to other designs. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 0 publications
1
24
3
Order By: Relevance
“…26,34,35 Further studies have found failure rates to be reduced when cantilever designs are used in preference to fixed/fixed designs. 36,37 Although all this evidence suggests that the RBB is an acceptable form of treatment, there is little evidence about the survival and clinical performance of RBBs when provided specifically for post-orthodontic hypodontia patients, and in particular the survival of RBBs replacing the commonly missing maxillary lateral incisor.…”
Section: Verifiable Cpd Papermentioning
confidence: 99%
“…26,34,35 Further studies have found failure rates to be reduced when cantilever designs are used in preference to fixed/fixed designs. 36,37 Although all this evidence suggests that the RBB is an acceptable form of treatment, there is little evidence about the survival and clinical performance of RBBs when provided specifically for post-orthodontic hypodontia patients, and in particular the survival of RBBs replacing the commonly missing maxillary lateral incisor.…”
Section: Verifiable Cpd Papermentioning
confidence: 99%
“…No orthodontic treatment was realized due to the fact that the patient refused to wear brackets. Finally an adhesive cantilever bridge 9 was seated in order to replace the missing upper left lateral incisor. Having then reestablished function and esthetics, as well as having solved the problem of sensitivity, the patient was kept with these restorations and under recall every 4 months up to the point of complete soft and hard tissue maturation.…”
Section: Clinical Proceduresmentioning
confidence: 99%
“…It has been reported that single abutment, single pontic, cantilever, resin bonded bridges have several advantages over multi-abutment resin bonded bridge designs 16 and that cantilevers had a greater median survival than all other designs. 17 De-bond rates of 20%, 16 21%, 18 17% 19 and 32% 15 have been reported. It has been proposed that the Rochette retainer design is more prone to debonding because of the relatively small retentive area per retainer, but the facility for easier removal, cleaning and rebonding is recognised.…”
Section: Discussionmentioning
confidence: 99%